Evaluating the United Nations Development Assistance Framework (UNDAF) as a strategic programming tool at the national level, with special reference to Egypt - Mahmoud, Rasha (AUC Knowledge Fountain, 2014)
The unique character of the United Nations (UN) imposes strategic challenges on the organization’s leadership and management structures at the national and the international level. In response to these challenges, the UN reform efforts, introduced in 1997, paved the way for the UN system effectiveness, efficiency and coherence. Emerging from the reform, the United Nations Development Assistance Framework (UNDAF) engages various development stakeholders in identifying and achieving national development priorities. This review found that the UNDAF is an effective strategic instrument that well-positions the UN at the national level and it enhances national capacities and supports national governments in identifying and achieving their development priorities within the context of the internationally agreed development goals and agreements. However, this evidence-based study found that the lack of national ownership of some governments obstructs the UNDAF formulation and implementation process. Notably, despite that some evidences indicate that the UNDAF could be a challenging process when UNCTs are not Delivering as One (DaO), this interview-based study found that the DaO approach could further complicate the process if it is not carefully studied based on country-specific contexts